Reformasi Birokrasi dan Good Governance : Studi Kasus pada DPM-PTSP Kota Medan - Windu Anggara; Sofyandi Lubis (Universitas 17 Agustus 1945, 2024)
This study examines the effectiveness of bureaucratic reform in achieving good governance at the Investment and One-Stop Integrated Services Agency (DPM-PTSP) of Medan City. The objective is to evaluate how bureaucratic reform impacts performance and transparency in public service delivery. The research method employed is qualitative, using a case study approach, involving indepth interviews and document analysis. The findings reveal that bureaucratic reform has positively influenced the efficiency, accountability, and transparency of DPM-PTSP Medan City. In conclusion, bureaucratic reform is a crucial instrument in achieving good governance in the public sector.